2009
DOI: 10.1292/jvms.71.839
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Four Virulence-Associated Genes of Campylobacter jejuni Isolates from Thai Broilers and Their Abilities of Adhesion to and Invasion of INT-407 Cells

Abstract: ABSTRACT. Campylobacter jejuni is a major cause of food borne pathogens in humans and a major reservoir for this pathogen is poultry. The C. jejuni in broilers was investigated from in the caeca of broilers. Twenty broiler/flock samples from 7 flocks were assessed. The average prevalence of C. jejuni was 65% in the broiler flocks. The adhesion and invasion ability of 48 strains of C. jejuni on INT 407 were studied. The adhesion and invasion ability of 48 Campylobacter isolates from caecal contents were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
2
10
0
3
Order By: Relevance
“…was calculated in the study (80.9%). In Thailand a high prevalence rate of Campylobacter jejuni was also observed from broilers flocks that correlated with the results of our study (65.0%) [4]. In the Netherlands a previous study showed that Campylobacter spp.…”
Section: Discussionsupporting
confidence: 92%
“…was calculated in the study (80.9%). In Thailand a high prevalence rate of Campylobacter jejuni was also observed from broilers flocks that correlated with the results of our study (65.0%) [4]. In the Netherlands a previous study showed that Campylobacter spp.…”
Section: Discussionsupporting
confidence: 92%
“…Each of these genes were found in 16.7-100% of Campylobacter isolates in this study. Chansiripornchai and Sasipreeyajan [42] reported dnaJ, cadF, pldA and ciaB virulence genes as 100, 76, 31 and 41% in C. jejuni isolates from broilers. In contrast to this study, higher prevalence rate for racR, dnaJ, cadF, pldA and ciaB was reported by Datta et al [29] as 85.7%, 100%, 100%, 100% and 100%, respectively.…”
Section: Aslantaşmentioning
confidence: 99%
“…Application of molecular tools, such as PCR (may help to avoid some of the limitations of current methods, where the hipO gene is specific for C. jejuni strains (Sinha et al, 2004). Table (3) and photo(1&2) showed the Occurrence of virulence genes of C. jejuni strains isolated fromthe examined samples of chicken meat andgiblets ,virulence genes cdtA, cdtB and cdt C , cdtA and cdtC ,cdtBand cdtC ,CdtA, CdtB and CdtC were present in 30% , 15%, 25%, 10% ,15 and 5 of examined of strain of c.jejuni respectively these genes are involved mainly in adhesion and invasion and they referred to as virulence factors from this point onwards ( Chansiripornchai and Sasipreeyajan, 2009). In conclusion, the highest incidence of Campylobacter strains was founded in chicken Breast with skin 7 28 5 20 0 0 0 0 0 0 3 12 Breast without skin 6 24 4 16 2 8 0 0 0 0 0 0 Thigh with skin 10 40 4 16 2 8 2 8 0 0 0 0 Thigh without skin 9 36 3 12 3 12 0 0 2 8 0 0 Liver 12 48 5 20 2 8 1 4 0 0 0 0 Gizzard 11 44 6 24 3 12 0 0 0 0 0 0 Total 55 liver and gizzard (80%).…”
Section: Discussionmentioning
confidence: 99%